(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The bipolar junction transistor (BJT) is similarly to the metal-oxide semiconductor field-effecttransistor (MOSFET) in that it is a three-terminal semiconductor device with many different uses. In thedesign of integrated circuits (ICs), which contain whole circuits manufactured on a single silicon chip, theMOSFET has become by far the most extensively used electronic device. Silicon (Si) technology is used inCMOS processes since it is the most developed of the semiconductor technologies. In addition to beingthe most inexpensive semiconductor material, silicon also has the advantage of being widely available.The addition of a small number of impurity atoms can alter its characteristics. Most power MOSFETsprevent the parasitic bipolar transistor from turning on by shorting the N+ source P-body junctionthrough the source metallization.